Association of hematocrit with blood pressure and hypertension. Issue 6 (20th January 2017) - Emamian, Marzieh; Hasanian, Seyed Mahdi; Tayefi, Maryam; Bijari, Moniba; Movahedian far, Faeze; Shafiee, Mojtaba; Avan, Amir; Heidari‐Bakavoli, Alireza; Moohebati, Mohsen; Ebrahimi, Mahmoud; Darroudi, Sousan; Zamani, Parvin; et al.
Abstract : Background: Hypertension (HTN) is a risk factor for stroke, renal failure, and cardiovascular disease. The association between biochemical and hematological parameters with high blood pressure may provide a more precise approach to risk prediction conferred by HTN in these patients. Objective: The aim of current study was to explore whether biochemical and hematological parameters are associated with HTN in a cohort study with a 7‐year follow‐up. Materials and Methods: A total of 9808 individuals were enrolled and recruited as part of the Mashhad Stroke and Heart Atherosclerotic Disorders (MASHAD) cohort study, and biochemical and hematological factors were measured in all subjects. Univariate and multivariate logistic regression analysis were performed to determine the association of biochemical and hematological parameters with HTN. Results: Several biochemical parameters including fasting plasma glucose (FBG), serum high‐sensitivity C‐reactive protein (hs‐CRP), triglyceride (TG), total cholesterol (TC), low‐density lipoprotein cholesterol (LDL‐C), and uric acid were increased in hypertensive participants. In contrast, serum high‐density lipoprotein cholesterol (HDL‐C) was lower in hypertensive individuals. Furthermore, we demonstrated that hematological parameters including white blood cell (WBC) count, red blood cell (RBC) count, hemoglobin (HGB), hematocrit (HCT), and mean corpuscular hemoglobin (MCH) were higher in the hypertensive group compared to the control group. But mean corpuscular volume (MCV), and red cell distribution width (RDW), were decreased in the hypertensive group. Furthermore, our results strongly suggested that among these parameters, hematocrit was the independent risk factor for hypertension in the population. Conclusion: We demonstrated the association of altered biochemical and hematological factors with hypertension supporting the value of emerging markers for early prediction of high blood pressure in prone individuals.